Habituation of Disciplinary Character Traits in Early Childhood: A Case Study from RA Arif Rahman Hakim Yogyakarta - Nadlifah , Nadlifah; Siregar, Suaibatun Aslamiyah; Ismaiyah, Nurul; Maulidah, Winda Syafaatin (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2023)
This research constitutes a descriptive qualitative study aimed at delving deeper into the habituation of discipline traits in children and the efforts undertaken by teachers to shape these discipline character habits within the B1 group of Arif Rahman Hakim Kindergarten, Yogyakarta. Research data was collected through various methods, including participatory observation, semi-structured interviews, and documentation from supervising teachers, the school principal, as well as 15 students. Findings indicate the necessity of nurturing early childhood growth, emphasizing the pivotal role of habitualizing discipline at RA Arif Rahman Hakim. Key indicators of children's discipline encompassed time management, rule adherence, behavior, and religious practices. Educators effectively used modelling and habituation methods, with collaboration among teachers, parents, and the school environment being instrumental in promoting positive behaviors. The study underscores the significance of schools and teachers in shaping disciplinary character traits, relying on a blend of firm guidance, democratic discipline approaches, and steadfast value system reinforcement. These insights present a roadmap for other institutions and educators aiming to enhance character education quality. Further studies are suggested to delve deeper into the intricate processes and factors influencing the development of children's disciplinary traits.